Edukasi dan Simulasi Kebencanaan di SDN 1 Punggul Sidoarjo - Ainun Ganisia; Arkha Rosyaria Badrus; Rakhmalia Imeldawati; Nurul Fathiyyah (Rena Cipta Mandiri, 2025)
Schools are strategic settings for cultivating disaster awareness from an early age, yet school communities often lack adequate knowledge, evacuation skills, and coordination mechanisms. This community service program aimed to strengthen disaster preparedness at SDN 1 Punggul, Sidoarjo, through education, demonstration, simulation, and institutional reinforcement. The program was conducted from 11 March to 2 May 2025 using a participatory approach that included partner coordination, development of communication and educational media, interactive counseling, drop-cover-evacuate practice, basic first aid, drills using evacuation routes and assembly points, and establishment of a School Disaster Preparedness Team. Evaluation used quizzes or question-and-answer sessions, drill observation, and participant feedback. The activities improved understanding of hazards and early warnings, supported more orderly evacuation skills, produced better coordinated collective responses, increased familiarity with emergency facilities, and generated educational media and a clearer division of preparedness roles. This school-based program can support sustained preparedness habits when reinforced through periodic drills and standardized evaluation.